2016
DOI: 10.1021/acssuschemeng.6b01075
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable, Reusable, and Superhydrophobic Aerogels from Microfibrillated Cellulose for Highly Effective Oil/Water Separation

Abstract: The development of sustainable and efficient absorbents for oil and organic pollutants cleaning is an attractive and challenging work. Here, novel superhydrophobic microfibrillated cellulose aerogels (HMFCAs) with high lipophilicity, ultralow density (≤5.08 mg/cm3), superior porosity (≥99.68%) as well as extremely high mechanical stability were successfully prepared from microfibrillated cellulose aerogels (MFCAs) via a facile and environmentally friendly silanization reaction in liquid phase. The superhydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(91 citation statements)
references
References 46 publications
3
86
0
Order By: Relevance
“…The reusability, durability and efficiency of oil water separation most likely stems from the strong covalent bonds on the cellulose surface as well as the excellent mechanical properties of the cellulose nanocrystals such as the strength, stiffness and wear resistance. Similar to the study by Zhou et al [51], these works demonstrate the capability of superhydrophobic CNCs when geared towards applications such as water contaminant separation.…”
Section: Cellulose Nanocrystals In Wettable Applicationssupporting
confidence: 73%
See 2 more Smart Citations
“…The reusability, durability and efficiency of oil water separation most likely stems from the strong covalent bonds on the cellulose surface as well as the excellent mechanical properties of the cellulose nanocrystals such as the strength, stiffness and wear resistance. Similar to the study by Zhou et al [51], these works demonstrate the capability of superhydrophobic CNCs when geared towards applications such as water contaminant separation.…”
Section: Cellulose Nanocrystals In Wettable Applicationssupporting
confidence: 73%
“…Zhou et al recently developed a superhydrophobic micro fibrillated cellulose aerogel (HMFCA) to efficiently separate oil from water [51]. In this study, silanization in an ethanol solution containing methyltriethoxysilane (MTES) was used to modify the aerogel by introducing polysiloxane groups on the surface of the HMFCAs.…”
Section: Cellulose Nanocrystals In Wettable Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Many researchers have reported significant increases in the fracture stress of bio-based composites after incorporating MFC. [1,8,9] For example, with the addition of 30wt% MFC derived from bamboo, the fracture stress and Young's modulus were increased from 20.2 MPa to 59.3 MPa and from 596 MPa to 1816 MPa, respectively. [10] Nakagaito and Yano reported that phenolic composites containing 20wt% MFC from kraft pulp to have Young's modulus of up to 370 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…First, superhydrophobic/superoleophilic oil sorbents with a remarkable mechanical durability are frequently used for water remediation . The sorbents typically consist of bulk materials such as polyurethane (PU) sponge, melamine sponge, delignified wood, 3D tubular boron nitride (BN) cellular‐network foams, cellulose aerogels, and carbon‐based composites …”
Section: Robust Superwettable Membranes For Oil–water Separationmentioning
confidence: 99%